2017
DOI: 10.24920/j1001-9294.2017.015
|View full text |Cite
|
Sign up to set email alerts
|

Can Fundus Fluorescein Angiography be Performed for Diabetic Patients on Oral Metformin?△

Abstract: Metformin is a kind of biguanide hypoglycemic agent that has been widely used in patients with diabetes mellitus. In clinical practice, whether metformin should be stopped before Fundus fluorescein angiography (FFA) remains largely unclear. Some endocrinologists suggest stop metformin before FFA. However, ophthalmologists do not always adopt this opinion in their practice. This situation may lead to disputes between physicians and patients. This article analyzed contrast-induced nephropathy(CIN) and the relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In addition, a single center observational study demonstrated that metformin therapy prior to elective CAG is safer in patients with preserved left ventricular ejection fraction of >40% or even with mild renal dysfunction (19). Likewise, in diabetic patients receiving metformin, no CIN has been reported after fundus fluorescein angiography (FFA) using fluorescein sodium (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a single center observational study demonstrated that metformin therapy prior to elective CAG is safer in patients with preserved left ventricular ejection fraction of >40% or even with mild renal dysfunction (19). Likewise, in diabetic patients receiving metformin, no CIN has been reported after fundus fluorescein angiography (FFA) using fluorescein sodium (20).…”
Section: Discussionmentioning
confidence: 99%